2012
DOI: 10.19173/irrodl.v13i3.1190
|View full text |Cite
|
Sign up to set email alerts
|

Teaching time investment: Does online really take more time than face-to-face?

Abstract: <span>Enrollments in online programs are growing, increasing demand for online courses. The perception that teaching online takes more time than teaching face-to-face creates concerns related to faculty workload.  To date, the research on teaching time does not provide a clear answer as to the accuracy of this perception. This study was designed to investigate which aspects, if any, are more time consuming for instructors teaching in the online environment.  Time logs were kept by four online instructors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…(9) came in last place (apology) Sometimes for completing the lecture to accomplish personal work) with a mean (2.00). This result indicates that the subject of distance education is a new topic as a result of the health conditions that the countries of the world are going through, including the Kingdom of Saudi Arabia, and accepting the change in the method of education needs time for the two parties to the educational process (the faculty member and the student) , and therefore The degree of commitment of faculty members was medium, The result of the present study is consistent with that of Buzbindir (2019),A the better their time planning and effective use of time, the more their significant and insignificant cyberloafing behavior decreased, and The current study agrees with the Van deVord & Pogue (2012)…”
supporting
confidence: 88%
“…(9) came in last place (apology) Sometimes for completing the lecture to accomplish personal work) with a mean (2.00). This result indicates that the subject of distance education is a new topic as a result of the health conditions that the countries of the world are going through, including the Kingdom of Saudi Arabia, and accepting the change in the method of education needs time for the two parties to the educational process (the faculty member and the student) , and therefore The degree of commitment of faculty members was medium, The result of the present study is consistent with that of Buzbindir (2019),A the better their time planning and effective use of time, the more their significant and insignificant cyberloafing behavior decreased, and The current study agrees with the Van deVord & Pogue (2012)…”
supporting
confidence: 88%
“…Because of the current situation, instructors moved quickly from the traditional teaching to online teaching, But, does this sudden transition make them to dedicate more time for COVID-19 and digitizing accounting lecturing or not? Faculty members perceive online teaching more time consuming than the traditional one (Van de Vord and Pogue, 2012). Virtual learning requires instructors to incorporate online activities, which have positive impact on students' engagement, attitude and performance (Vatovec and Balser, 2009).…”
Section: Lecturing Timing During Covid-19 Pandemicmentioning
confidence: 99%
“…A study found that online teaching takes a minimum of 14% more time than face‐to‐face. However, other studies argue that time per‐student is similar to face‐to‐face delivery (Hislop & Ellis, 2004), while others found that online teaching takes, on average 11.28 min less per student than face‐to‐face classes (Van de Vord & Pogue, 2012). Every class is different, and this variability likely stems from the subtle differences between courses.…”
Section: Discussionmentioning
confidence: 98%